Co Line Emission Surfaces and Vertical Structure in Midinclination Protoplanetary Disks - Perez-Marquez, S (Institute of Physics, 2022)
High spatial resolution CO observations of midinclination (≈30°-75°) protoplanetary disks offer an opportunity to study the vertical distribution of CO emission and temperature. The asymmetry of line emission relative to the disk major axis allows for a direct mapping of the emission height above the midplane, and for optically thick, spatially resolved emission in LTE, the intensity is a measure of the local gas temperature. Our analysis of Atacama Large Millimeter/submillimeter Array archival data yields CO emission surfaces, dynamically constrained stellar host masses, and disk atmosphere gas temperatures for the disks around the following: HD 142666, MY Lup, V4046 Sgr, HD 100546, GW Lup, WaOph 6, DoAr 25, Sz 91, CI Tau, and DM Tau. These sources span a wide range in stellar masses (0.50-2.10 M ⊙), ages (∼0.3-23 Myr), and CO gas radial emission extents (≈200-1000 au). This sample nearly triples the number of disks with mapped emission surfaces and confirms the wide diversity in line emitting heights (z/r ≈ 0.1 to ≳0.5) hinted at in previous studies. We compute the radial and vertical CO gas temperature distributions for each disk. A few disks show local temperature dips or enhancements, some of which correspond to dust substructures or the proposed locations of embedded planets. Several emission surfaces also show vertical substructures, which all align with rings and gaps in the millimeter dust. Combining our sample with literature sources, we find that CO line emitting heights weakly decline with stellar mass and gas temperature, which, despite large scatter, is consistent with simple scaling relations. We also observe a correlation between CO emission height and disk size, which is due to the flared structure of disks. Overall, CO emission surfaces trace ≈2-5× gas pressure scale heights (Hg) and could potentially be calibrated as empirical tracers of Hg. © 2022. The Author(s). Published by the American Astronomical Society.